The linkage between global financial crises, corporate social responsibility and climate change: unearthing research opportunities through bibliometric reviews - Chebo, Abdella K.; Dhliwayo, Shepherd; Batu, Muhdin M. (Frontiers in Climate, 2024)
Financial matters, corporate social responsibility (CSR), climate change, and other sustainable solutions all work in tandem. In order to provide a thorough understanding of the integration between various components during crises, it is necessary to provide knowledge of the interaction between financial, societal, and environmental aspects. In order to accomplish this, hundreds of papers were examined and presented using bibliometric analysis. The study demonstrated that, when examining financial crises in relation to CSR and climate change, sustainability issues were clearly examined. Sustainability, environmental economics, governance approaches, and sustainable development are some of the main issues in this comprehensive subject. Besides, the emerging topics that need more research include organizational resilience, global financial crises, and sustainable performance, while there are no specific themes developed in the subject matter that integrate financial crises, CSR, and climate change. Thus, future researchers need to provide new insights on the integration of these concepts.